2016
DOI: 10.1038/ejhg.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Consent for newborn screening: parents’ and health-care professionals’ experiences of consent in practice

Abstract: Consent processes for newborn bloodspot screening (NBS) are variable, with a lack of descriptive research that depicts how the offer of NBS is made to parents. We explored the experience, in practice, of consent for NBS. Semistructured interviews in two Canadian provinces were held with: (1) parents of children offered NBS (n = 32); and (2) health-care professionals involved in the NBS process (n = 19). Data on recollections of NBS, including consent processes, were utilized to identify emerging themes using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
(61 reference statements)
2
31
0
Order By: Relevance
“…Results have shown that Czech mothers in the study sample have only limited NBS awareness and three months post-delivery around one fifth of mothers do not recall any information about NBS. Limited awareness and knowledge about NBS has been demonstrated by previous international studies that have focused on education about NBS [10,11,[17][18][19][20][21][22][23], the informed consent process [7,[24][25][26], and the impact of positive and/or false positive NBS results [2,4,5,9,27]. These studies have been performed in Canada [7,11], the US [2][3][4][5]18,20], the UK [22,23,25,26], Australia [10,17], the Netherlands [24] and Saudi Arabia [21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Results have shown that Czech mothers in the study sample have only limited NBS awareness and three months post-delivery around one fifth of mothers do not recall any information about NBS. Limited awareness and knowledge about NBS has been demonstrated by previous international studies that have focused on education about NBS [10,11,[17][18][19][20][21][22][23], the informed consent process [7,[24][25][26], and the impact of positive and/or false positive NBS results [2,4,5,9,27]. These studies have been performed in Canada [7,11], the US [2][3][4][5]18,20], the UK [22,23,25,26], Australia [10,17], the Netherlands [24] and Saudi Arabia [21].…”
Section: Discussionmentioning
confidence: 99%
“…However the evidence demonstrates slow progression towards appropriate parental NBS education and consent. [7]. The issue of explicitly informed parental consent is of particular importance with the emergence of next-generation sequencing technologies and its possible application to NBS testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Some parents refuse newborn screening because of concerns about pain in their infants. 2,3 Evidence-based guidelines recommend that health care professionals support use of breastfeeding, skin-to-skin care, or sucrose or glucose to reduce newborn pain. 4,5 However, these strategies are underused, and some health care professionals believe that mothers do not wish to be present during painful procedures, 6 which means that many newborns suffer unnecessarily during painful procedures.…”
mentioning
confidence: 99%